2021
DOI: 10.1016/j.cattod.2020.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Deep hydrodesulfurization of 4,6-dimethydibenzothiophene over CoMoS/TiO2 catalysts: Impact of the TiO2 treatment

Abstract: Mesostructured titania as support for the CoMoS active phase in deep hydrodesulfurization (HDS) of 4,6-dimethydibenzothiophene (4,6-DMDBT) leads to an increase of the intrinsic HDS activity and a higher selectivity for direct desulfurization (DDS) for HDS reaction in contrast with the conventional CoMoS/alumina catalyst. The temperature treatment of the mesostructured TiO 2 support, modifies the catalyst's activity for the transformation of 4,6-DMDBT. The higher total and HDS activities were obtained after tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…However, the same tendency was noted for the activity per atom of Mo; we can thus assume that the difference in activity and selectivity may have been due to a modification of the active sites which are the molybdenum atoms. This involved different interactions with the support because of the presence of the amorphous phase, which will lead to modifications of the electronic properties, as already observed with TiO 2 [20]. Indeed, in a recent study [29], we showed that the prepared amorphous mesostructured ZrO 2 exhibited a high thermal stability up to 400 • C. We can thus assume that the change in selectivity was mainly due to the presence of this amorphous phase, which likely modified the intermediates of reaction by favoring the ones involved in the direct rupture of the C-S bond [5], and/or by modifying the properties of the active phase.…”
Section: Catalytic Activity For Hydrodesulfurization Of 46dmdbt Hdsmentioning
confidence: 76%
See 3 more Smart Citations
“…However, the same tendency was noted for the activity per atom of Mo; we can thus assume that the difference in activity and selectivity may have been due to a modification of the active sites which are the molybdenum atoms. This involved different interactions with the support because of the presence of the amorphous phase, which will lead to modifications of the electronic properties, as already observed with TiO 2 [20]. Indeed, in a recent study [29], we showed that the prepared amorphous mesostructured ZrO 2 exhibited a high thermal stability up to 400 • C. We can thus assume that the change in selectivity was mainly due to the presence of this amorphous phase, which likely modified the intermediates of reaction by favoring the ones involved in the direct rupture of the C-S bond [5], and/or by modifying the properties of the active phase.…”
Section: Catalytic Activity For Hydrodesulfurization Of 46dmdbt Hdsmentioning
confidence: 76%
“…Amorphous mesostructured ZrO 2 was prepared according the procedure described in reference [29]. The wet impregnation used CoN 2 O 6 , 6H 2 O, 99.00% Si (Sigma-Aldrich Chemie S.a.r.l., Saint-Quentin Fallavier, France) and (NH 4 ) 6 Mo 7 , 6H 2 O, 99.98% (Sigma-Aldrich Chemie S.a.r.l., Saint-Quentin Fallavier, France) precursors and was performed under the same conditions as the ones reported in Reference [20].…”
Section: Materials Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of sulfur-free fuel oil from petroleum materials, especially from low-grade diesel, has been a pressing mission because of increasingly stringent standards on the maximum sulfur content of diesel fuel. However, the production of ultraclean diesel is limited by the refractory sulfur compound 4,6-di­methyl­di­benzo­thio­phene (4,6-DMDBT) with alkyl groups at the 4 and 6 positions that resulted in the space-shield effect. , Industrially, hydrodesulfurization (HDS) is the most effective and widely used desulfurization technology to reduce the sulfur concentration of fuel oil to below 10 ppm. Co­(Ni)­MoS supported over Al 2 O 3 is a commonly used HDS catalysts in the petroleum refining industry.…”
Section: Introductionmentioning
confidence: 99%